1991
DOI: 10.1136/gut.32.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different laminin binding proteins in basolateral cell membranes of human colorectal carcinomas and normal colonic mucosa.

Abstract: The adhesive properties of tumour cells to laminin, the major glycoprotein of basement membranes, play a crucial part in the complex process of tumour invasion and metastasis. We therefore investigated the expression of laminin binding proteins in isolated basolateral cell membranes of human colorectal carcinomas and the adjacent normal colonic mucosa. Cell membrane binding assays and immunoblotting experiments showed appreciable quantitative and qualitative differences in the expression of these proteins in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…could not be identified in basolateral cell membranes of the small intestinal epi thelium. However, in addition to 66-to 69-kD laminin-binding proteins in epithelial cell membranes of human colon carcinomas laminin-binding proteins with higher molec ular weights were identified [11,27], These binding proteins may be related to the family of integrins. The integrins which serve as a link between extra-and intracellular compo nents, mainly recognize binding sites that include the tripeptide Arg-Gly-Asp (RGD), a sequence which is common to many extra cellular and plasma proteins such as fibronectin, vitronectin and von Willebrand fac tor [28] and has recently been described in the A-chain of the laminin molecule [29], A member of the integrin receptor family with an Mr of 140 kD after reduction, which may also function as a laminin receptor, was re cently identified in a human glioblastoma cell line [14], The presence of other laminin binding proteins in colon carcinomas may alter the affinity of cells for laminin or mod ulate their interaction with other extracellu lar matrix components.…”
Section: Discussionmentioning
confidence: 99%
“…could not be identified in basolateral cell membranes of the small intestinal epi thelium. However, in addition to 66-to 69-kD laminin-binding proteins in epithelial cell membranes of human colon carcinomas laminin-binding proteins with higher molec ular weights were identified [11,27], These binding proteins may be related to the family of integrins. The integrins which serve as a link between extra-and intracellular compo nents, mainly recognize binding sites that include the tripeptide Arg-Gly-Asp (RGD), a sequence which is common to many extra cellular and plasma proteins such as fibronectin, vitronectin and von Willebrand fac tor [28] and has recently been described in the A-chain of the laminin molecule [29], A member of the integrin receptor family with an Mr of 140 kD after reduction, which may also function as a laminin receptor, was re cently identified in a human glioblastoma cell line [14], The presence of other laminin binding proteins in colon carcinomas may alter the affinity of cells for laminin or mod ulate their interaction with other extracellu lar matrix components.…”
Section: Discussionmentioning
confidence: 99%
“…As originally described,6 integrins were divided into three subfamilies, each with a common 13 subunit capable of associating with a specific group of a subunits. More recent works have shown that there are at least 11 different a subunits and eight 13 subunits, and that certain a subunits can combine with more than one 13 subunit.7 The 131, 12, and 13 subunits can associate with several distinct a subunits, and define the three integrin subfamiliesthe VLA (very late activation antigens) protein family, the LEU-CAM (leucocyte cell adhesion molecule) family, and the cytoadhesions, respectively.8 The first subfamily comprises at least six related complexes, each consisting of a [3I chain with a distinct a chain companion. Most of these integrins are promiscuous receptors because they bind to various matrix proteins.7 Members ofthe VLA subfamily include receptors for fibronectin (VLA-3, VLA-4, and VLA-5), laminin (VLA-1, VLA-2, VLA-3, and VLA-6) and collagen types I and IV (VLA-1, VLA-2, and VLA-3).9' However, VLA-5 and VLA-6 seem to be specific for fibronectin and laminin, respectively.7' The 12 subfamily of integrins, also termed LEU-CAMs or the CD18 antigens, consists of three leukocyte adhesion receptors.7 The 13 subfamily of integrins, also known as cytoadhesions, consists of vitronectin receptor (av/133) and the platelet glycoprotein Ilb/IIIA (aIIb/3) complex (reviewed in ')).…”
mentioning
confidence: 99%
“…v mal cells. Basolateral membranes of epithelial cells from colorectal carcinomas have been reported to bind 5 to 8 times more laminin-1 than basolateral cell membranes of the adjacent normal colonic epithelium, and the expression of the so-called 'Mr 67 kD laminin receptor' is three to four times higher in colorectal carcinomas than in normal colonic epithelium [30]. The predominant role of laminin in the invasion process led us to study the colon carcinoma cell behavior when interacting with laminin-1, in vivo.…”
Section: Fig 7a-d Expression Of Vimentin By Rare C5 (A) and M4 (B) Cmentioning
confidence: 99%